2022
DOI: 10.1016/j.ypmed.2022.106961
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of the COVID-19 pandemic on cancer screening in a central Canadian province

Abstract: We evaluated the impact of COVID-19 on cancer screening in Manitoba, Canada using an interrupted time series (ITS) design and data from Manitoba's population-based, organized cancer screening programs from April 2020 to August 2021. In June 2020 (breast screening was suspended during April and May 2020), there was a 54% decrease between the predicted (i.e., observed data produced from regression models) and expected (i.e., counterfactual values produced for the COVID-19 period by assuming COVID-19 did not occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 16 publications
2
40
0
1
Order By: Relevance
“…During the COVID-19 pandemic, Quebec regulations prioritized cancer services toward patients undergoing treatments, causing further waiting for patients awaiting diagnoses. This worsened existing delays in Canadian breast cancer clinics ( Decker et al, 2022 ; Farah et al, 2021 ; Gouvernement du Québec, 2020 ) and could, in turn, further impact patients’ psychological well-being.…”
Section: Background and Purposementioning
confidence: 99%
“…During the COVID-19 pandemic, Quebec regulations prioritized cancer services toward patients undergoing treatments, causing further waiting for patients awaiting diagnoses. This worsened existing delays in Canadian breast cancer clinics ( Decker et al, 2022 ; Farah et al, 2021 ; Gouvernement du Québec, 2020 ) and could, in turn, further impact patients’ psychological well-being.…”
Section: Background and Purposementioning
confidence: 99%
“…Given that the COVID-19 pandemic has prevented and continues to prevent women from engaging in cervical cancer screening, this may affect women’s report of their screening history and change the composition of women in our “underscreened” and “adequately screened” categories. It is not clear how this will affect our data as the COVID-19 pandemic’s effect on screening access in Canada is not well understood in most provinces and territories [93]. To address this issue, we will include an item asking those participants who report being underscreened whether the COVID-19 pandemic had prevented them from receiving screening, and sensitivity analyses will be performed to examine the pandemic’s impact on screening.…”
Section: Discussionmentioning
confidence: 99%
“…This could still have consequences described elsewhere such as more advanced diagnosis and delays in treatments that could affect patients' survival [9,[15][16][17]. This return to 2019 diagnostic capacity is not yet described in many articles, although some studies observed that screening programmes and cancer diagnosis returned close to pre-pandemic levels late 2020 [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…After the first wave of COVID-19, some restrictions were lifted in several countries and screening programmes were recovered, thus contributing to a change in cancer’s diagnostic trends. For instance, in a study in Canada, researchers observed that after a huge drop of cancer screening during the first months of COVID-19 pandemic, within a few months, programs and cancer management have been adapted to the new situation and one year later, the number of procedures reached pre-pandemic levels, suggesting that cancer diagnostic capacity could be returned to normal [11].…”
Section: Introductionmentioning
confidence: 99%